Lumbar disc degeneration and genetic factors are the main risk factors for low back pain in women: the UK Twin Spine Study. Issue 10 (6th June 2011) - Livshits, Gregory; Popham, Maria; Malkin, Ida; Sambrook, Philip N; MacGregor, Alex J; Spector, Timothy; Williams, Frances M K
Abstract : Objective: Low back pain (LBP) is a common musculoskeletal disorder, but it is still unclear which individuals develop it. The authors examined the contribution of genetic factors, lumbar disc degeneration (LDD) and other risk factors in a female sample of the general population. Material and Methods: A cross-sectional study was conducted among 2256 women (371 and 698 monozygotic and dizygotic twin pairs and 29 sibling pairs and 60 singletons) with a mean age of 50 years (18–84). A self-reported validated questionnaire was used to collect back pain data. Risk factors including body weight, smoking, occupation, physical exercise and MRI assessed LDD were measured. Data analysis included logistic regression and variance decomposition. Results: The major factors associated with LBP included genetic background, with OR approximately 6 if the monozygotic co-twin had LBP, or 2.2 if she was a dizygotic co-twin. In addition, LDD and overweight were highly significantly (p<0.001) associated with non-specific LBP. The single most important risk factor was the amount of LDD. After adjustment for other risk factors, the individuals who exhibited advanced LDD (90% vs 10%) had 3.2 higher odds of manifesting LBP. The data also showed a significant (p<0.001) genetic correlation between the LBP and LDD measurements, suggesting that approximately 11–13% of the genetic effects are shared by LDD and LBP. Conclusions: The main risk factors for reported episodes of severe and disabling LBP in UK women include the degree of LDD as assessed by MRI, being overweight and genetic heritability.